PERANCANGAN ANTENA MIKROSTRIP ARRAY PADA FREKUENSI 915 MHz UNTUK APLIKASI LONG RANGE (LoRa) - Lundu Holong Panjaitan; Emansa Hasri Putra (ABEC Indonesia, 2021)
The development of information technology is currently growing rapidly, especially in wireless communication for LoRa radios. So that various kinds of antennas have also been developed and one of the antennas used is the microstrip antenna. In this research, a successful microstrip array antenna at a frequency of 915 MHz can be applied to LoRa technology. Microstrip antennas have many advantages but also disadvantages, such as low gain. One way to overcome the low gain is to design a microstrip antenna with a 1x2 array method. This antenna uses a double layer PCB with FR-4 as a substrate. After the simulation and fabrication processes were carried out, the results were consecutive, namely the return loss value of -33.16 dB, VSWR 1.045, gain of 3,860 dBi. The fabrication results are the return loss value of -14.97 dB, VSWR 1.434, and a gain of 9.79 dBi. The simulated and measured radiation patterns are bidirectional. Keywords: Microstrip Antenna, array, bidirectional, LoRa.